2020
DOI: 10.26434/chemrxiv.12931703.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

π-Extended Helical Nanographenes: Synthesis and Photophysical Properties of Naphtho[1,2-a]pyrenes

Abstract: A mild and efficient synthesis of a broad scope of substituted naphtho[1,2-<i>a</i>]pyrene derivatives was accomplished in good yields using an InCl<sub>3</sub>/AgNTf<sub>2</sub>-mediated two-fold alkyne benzannulation reaction. HPLC enantiomeric separation was achieved and the interconversion barriers have been determined. The ECD spectra of two derivatives were recorded and interpreted through TD-DFT calculations. Raman spectra were also recorded and predicted through DFT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…5). 51 It was observed that the single enantiomers of these structures were prone to racemization at room temperature, and the racemization barriers for all of the synthesized derivatives were confirmed to be fairly low, all lying within a narrow range of 19.39 to 21.36 kcal mol −1 .…”
Section: π-Extended Helicenesmentioning
confidence: 89%
“…5). 51 It was observed that the single enantiomers of these structures were prone to racemization at room temperature, and the racemization barriers for all of the synthesized derivatives were confirmed to be fairly low, all lying within a narrow range of 19.39 to 21.36 kcal mol −1 .…”
Section: π-Extended Helicenesmentioning
confidence: 89%
“…The InCl 3 /AgNTf 2 catalytic system was used for the synthesis of pyrene‐based [4]helicenes (naphtho[1,2‐ a ]pyrenes) 134 a , b through a 2‐fold alkyne benzannulation reaction of compounds 133 (Scheme 39). [91] The reaction works well with various electron‐rich aryl (Ar) groups on acetylene termini. In cases of substrates 133 having less electron‐rich aryl groups (Ar=4‐ t ‐BuC 6 H 4 and 4‐Cl‐C 6 H 4 ) the only monocyclization products 135 c , d were obtained.…”
Section: Transition‐metal‐catalyzed Synthesesmentioning
confidence: 98%
“…Upon excitation at 320 nm, compound 132 exhibited a strong blue luminescence with λ max = 450 nm. The fluorescence quantum yields of 132 were notably high for helicene derivatives (23% in CH 2 Cl 2 and 17% in the solid state), which is a very desirable feature for applications in circularly polarized luminescent materials.The InCl 3 /AgNTf 2 catalytic system was used for the synthesis of pyrene-based[4]helicenes (naphtho[1,2a]pyrenes) 134 a,b through a 2-fold alkyne benzannulation reaction of compounds 133 (Scheme 39) [91]. The reaction works well with various electron-rich aryl…”
mentioning
confidence: 99%
“…In most cases, just this methodology has been used for the synthesis of pyrene–helicene hybrids. 11 a – c , h – j Among other synthetic methods used for pyrene-based helicenes, there are isolated examples of the Scholl reaction, 11 d transition metal-catalyzed [2 + 2 + 2] cycloaddition of triynes, 11 k Suzuki coupling of 2,2′-diiododiphenyl derivatives, 11 f and transition metal- 11 g or acid-catalyzed cycloisomerization of ortho -alkynylated biaryls. 11 e…”
Section: Introductionmentioning
confidence: 99%